A Chlamydia trachomatis OmcB C-Terminal Fragment Is Released into the Host Cell Cytoplasm and Is Immunogenic in Humans - Qi, Manli (American Society for Microbiology, 2011)

(untitled)
The Chlamydia trachomatis outer membrane complex protein B (OmcB) is an antigen with diagnostic and vaccine relevance. To further characterize OmcB, we generated antibodies against OmcB C-terminal (OmcBc) and N-terminal (OmcBn) fragments. Surprisingly, the anti-OmcBc antibody detected dominant signals in the host cell cytosol, while the anti-OmcBn antibody exclusively labeled intrainclusion signals in C. trachomatis-infected cells permeabilized with saponin. Western blot analyses revealed that OmcB was partially processed into OmcBc and OmcBn fragments. The processed OmcBc was released into host cell cytosol, while the OmcBn and remaining full-length OmcB were retained within the chlamydial inclusions. The organism-associated OmcB epitopes became detectable only after the C. trachomatis-infected cells were permeabilized with strong detergents such as SDS. However, the harsh permeabilization conditions also led to the leakage of the already secreted OmcBc and chlamydia-secreted protease (CPAF) out of the host cells. The OmcBc processing and release occurred in all biovars of C. trachomatis. Moreover, the released OmcBc but not the retained OmcBn was highly immunogenic in C. trachomatis-infected women, which is consistent with the concept that exposure of chlamydial proteins to host cell cytosol is accompanied by increased immunogenicity. These observations have provided important information for further exploring/optimizing OmcB as a target for the development of diagnosis methods and vaccines.